Att tala genom straff: Synen på straffets ändamål i Straffreformutredningen - Rosén,Julia (2025)
This thesis analyses how the purpose of punishment is articulated in ”Straff- reformutredningen”(the report for the proposed criminal law reform in Swe- den, SOU 2025:66). The aim is to examine which penal theories gain the greatest influence in the report and what this direction reflects in terms of underlying conceptions of the purpose of punishment. Particular attention is paid to how punishment – especially imprisonment – is justified in a context where crime rates have not increased at a pace corresponding to the overall growth of punishment. A key premise is therefore that factors other than crime levels, including a more severe view of certain forms of criminality, may underlie the reform. The thesis is grounded in social constructivism and post-structuralism and employs a discourse-analytical approach, primarily Carol Bacchi’s WPR method (What’s the Problem Represented to be?). This method is used to analyse how problems and solutions are constructed in the report, and what discourses this reveals. The analysis is supplemented by a legal-analytical method in order to situate the discourse within a criminal law context. As comparative material, historical parliamentary documents from two earlier major periods of penal reform are also included and analysed using the same discourse-analytical approach: the introduction of the cellular prison system in the nineteenth century and the legislative work leading to the 1965 Penal Code during the twentieth century. These reforms are examined to illumi- nate how conceptions of the purpose of punishment have shifted over time and to enable a historical comparison with the present reform. The analysis demonstrates that the report largely constructs the current state of criminality in Sweden as system-threatening and presents a more repres- sive penal system as a necessary response. Although the reform to some ex- tent discusses general and individual deterrence, its reasoning is to a signifi- cant degree characterised by elements associated with absolute theories of punishment. The most prominent of these are retribution, redress for victims and the communicative function of punishment. The victim–perspective is given a central role in the report and, in certain respects, serves to downplay the lack of empirical support for the crime-preventive effects of harsher pu- nishments. The thesis further shows that the reform only to a limited extent problemati- ses the practical consequences of a substantial expansion of imprisonment, such as its effects on recidivism, correctional services, and humanitarian principles. Instead, the symbolic and communicative significance of pu- nishment emerges as particularly important. The analysis indicates that the report marks a shift in criminal policy, whereby the legitimacy of pu- nishment is increasingly grounded in its expression of moral judgment rat- her than in evidence-based crime-preventive effects.
Keywords: Straffrätt; rättshistoria; socialkonstruktivism; poststrukturalism; diskursanalys; WPR; straffteori; straffreform; Straffreformutredningen; SOU 2025:66